A new Batillipedidae (Tardigrada, Arthrotardigrada) from Argentina - Menechella, Agustín G.; Bulnes, Verónica N.; Cazzaniga, Néstor J. (Zootaxa, 2015)
A new species of marine tardigrade, Batillipes acuticauda sp. n., has been found in midlittoral sand sediments collected at Monte Hermoso beach (Buenos Aires province, Argentina). The new species differs from all other members of Batillipedidae by its combination of caudal apparatus, lateral processes and toe patterns. It is the first description of an arthrotardigrade from Argentina.